Features of the integration process in Kazakhstan’s food industry - PRITVOROVA, Tatyana Petrovna; NEVMATULINA, Zarema Anvarovna (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
This article is concerned with the problems of integration processes in the food industry of the Republic of Kazakhstan. The author analyzes the current situation in sectors of food and processing industries. The integration process in corporate-level food industry is described; it was done on the basis of available official statistics on enterprises activity with foreign capital in Kazakhstan. Development problems of food industry, including joint ventures are revealed, possible measures to address them are highlighted. The author concludes that the need to create well equipped territories in the form of industrial zones, which would be close to sources of raw materials, and, simultaneously, to markets would be a positive impetus for development of joint ventures in the food industry.